The Institutions of Turkification and Assimilation in the Eyes of Armenian Orphans Who Fled Them - Peroomian, Rubina (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Although Armenian orphans are the focus of this paper, taken in a broader context, the treatment of Greek, Assyrian, and Armenian orphans—with all commonalities and differences— is a signifier of intent to destroy targeted groups of people as the Genocide Convention defines. This paper addresses the methods the Ottoman government undertook and the supplementary measures necessary in the implementation process of dealing with the myriad of children within the policy of total extermination. This involved setting up Turkish orphanages, some euphemistically called mektebs (religious schools)—with their brutal methods of forced conversion—pushing them into Muslim households—with all the torture and molestations that came with it but also serving the ulterior motive of improving the race—as institutions of Turkification, and in addition, the abhorring treatment of these children, torturing, raping, killing, along the roads of deportation. It will shed light on the experiences of these children in defined categories of victimization, those who lost their lives in this machination, those who survived and reached the outside world or continued living in Turkey as Muslims, true or pretending, as well as Christians upholding their faith against all odds. Based on interviews and first- person accounts of these orphans and newer studies on the state of mind of their offspring, this paper will outline the short-term effects, having turned this generation mostly into one that is socially dead unable to fully contribute to the perpetuation of the Armenian nation, as well as the long-term, that is the transgenerational effects of the genocide, a psychological burden upon the nation aggravating the situation and blocking the process of healing to begin. The Genocide Convention does not project the effects of these genocidal treatments which the Armenian nation still struggles to overcome.
Keywords: History